CTIM-29. CLINICAL EVALUATION OF CHLOROTOXIN-DIRECTED CAR T CELLS FOR PATIENTS WITH RECURRENT GLIOBLASTOMA. (12th November 2021) - Brown, Christine; Blanchard, M Suzette; Aftabizadeh, Maryam; Hibbard, Jonathan; Dodia, Ramsinh; Lingaraju, Chetan Raj; Starr, Renate; D'Apuzzo, Massimo; Forman, Stephen J; Portnow, Jana; Ressler, Julie A; Stiller, Tracey; et al.
Abstract: Chlorotoxin (CLTX), a peptide component of scorpion venom, exhibits selective and broad binding to glioblastoma (GBM) and other tumors with minimal activity against non-malignant cells. We have developed a novel CAR that utilizes CLTX as the tumor targeting domain. Preclinical studies established that CLTX-CAR T cells target GBM through recognition of a receptor complex incorporating membrane-bound matrix metalloprotease-2 (MMP-2). Here, we report initial clinical findings for our phase I trial evaluating safety and bioactivity of CLTX-CAR T cells in patients with MMP2+ recurrent GBM (NCT04214392). Weekly infusions of CLTX-CAR T cells are delivered locoregionally, either directly into the tumor cavity (ICT; Arm 1), or in combination with intracerebroventricular (ICV) delivery (dual ICT/ICV; Arm 2). At this interim analysis, four participants have received at least three cycles of CLTX-CAR T cells ICT (Arm 1; 3-8 cycles) at dose level 1 (DL1; 4M, 20M, 20M CAR T cells per cycle). None of the participants experienced dose limiting toxicity (DLT) during the DLT evaluation period of 28-days, although one participant experienced a serious adverse event of grade 3 cerebral edema, possibly attributed to CAR T cells. Overall, Arm 1-DL1 was well-tolerated, and the next patient cohort will be treated on Arm 2-DL1 (dual ICT/ICV; 8M, 40M, 40M CAR T cells per cycle), as per protocol design. Disease response was assessed by RANO, overall survival, and time to progression; three of four participants achieved a best response of stable disease. Liquid biopsy detected persistent CAR T cells in the tumor cavity throughout treatment, suggesting that the therapeutic cells are not immunogenic. Ongoing studies are evaluating biomarkers of response and resistance, including CAR T cell activation and inflammatory cytokines. This clinical study provides first-in-human evidence for the safety and feasibility of CLTX-CAR T cells as a new class of toxin-based CARs for treatment of GBM.